1987
DOI: 10.1159/000234175
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of a Guinea Pig Lymphocyte Cell Surface Antigen of Defined Function, as Detected by the Mouse Monoclonal Antibody MSgp 1

Abstract: A mouse anti-guinea pig monoclonal antibody, designated MSgp 1, was derived from a fusion between NS-1 myeloma cells and splenocytes hyperimmunised with guinea pig thymocytes. The MSgp 1 determinant is expressed by a subset of small thymocytes and lymph node T cells which participate in mixed leukocyte reactions. The determinant is modulated by antigen in vivo, and MSgp 1 antibody will prevent MHC class II driven proliferation in vitro. In addition, MSgp 1 reacts with a minor population of lymph node B cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1988
1988
1998
1998

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…A further immunization with 2 x 10s cells obtained as above was given via the same route on day 14. Five days later, the sensitized spleen was excised and the splenocytes fused to NS-1 mouse myeloma cells (Flow Laboratories) as previously described [Healey, et al, 1987]. The resultant hybridomas were screened by immunocytochemistry on normal guinea pig lymph node sections and positive hybridomas cloned by limiting dilution.…”
Section: Mitogenmentioning
confidence: 99%
“…A further immunization with 2 x 10s cells obtained as above was given via the same route on day 14. Five days later, the sensitized spleen was excised and the splenocytes fused to NS-1 mouse myeloma cells (Flow Laboratories) as previously described [Healey, et al, 1987]. The resultant hybridomas were screened by immunocytochemistry on normal guinea pig lymph node sections and positive hybridomas cloned by limiting dilution.…”
Section: Mitogenmentioning
confidence: 99%
“…T Lymphocytes were enriched by separation of whole lymph node cells on the basis of T cell adherence to nylon wool as previ ously described by Healey et al [1987b],…”
Section: T Lymphocytesmentioning
confidence: 99%
“…This system was used to quantitate the expres sion of the three monoclonal antibodies on B cells (i.e., those cells expressing surface immunoglobulin). A detailed methodology has been published previously [Healey et al, 1987b]. …”
Section: Double Immunofluorescence O F Lymph Node Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results showed that the increased proportion of small lymphocytes was limited to Vac animals only. In this regard, Healey, Parker and Turk (1987) have described two distinct populations of SLN T cells in guineapigs based on FSC of flow cytometry. Activated T cells that mediate contact sensitivity in the DNFB (2,4-dinitrofluorobenzene) model are of low FSC, i.e.…”
Section: Discussionmentioning
confidence: 99%